2018
DOI: 10.1038/s41598-018-26493-3
|View full text |Cite
|
Sign up to set email alerts
|

The invasion of abandoned fields by a major alien tree filters understory plant traits in novel forest ecosystems

Abstract: The abandonment of agricultural use is a common driver of spontaneous reforestation by alien trees. The N-fixing black locust (Robinia pseudoacacia L.) is a major alien invader of old fields in Europe. Here we show that canopy dominance by this tree may filter the frequency distribution of plant functional traits in the understory of secondary woodlands. Higher soil C/N ratio and available P are associated with black locust stands, while higher soil phenols associate with native tree stands. These environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 62 publications
0
17
1
Order By: Relevance
“…Our findings seem to contradict the idea that invasive plants increase soil fertility in invaded sites [19,20,23,34]. On one hand, such pattern can be partially explained by an increased consumption effect resulting from the addition of S. gigantea plants in our artificially invaded communities.…”
Section: Direct and Indirect Effects Of Functional Diversity And S Gcontrasting
confidence: 98%
See 1 more Smart Citation
“…Our findings seem to contradict the idea that invasive plants increase soil fertility in invaded sites [19,20,23,34]. On one hand, such pattern can be partially explained by an increased consumption effect resulting from the addition of S. gigantea plants in our artificially invaded communities.…”
Section: Direct and Indirect Effects Of Functional Diversity And S Gcontrasting
confidence: 98%
“…However, if considered in the long term, effects of this invasive species on native plants emergence rates and biomass production can reduce diversity of invaded communities by competitive exclusion of native species, thus deteriorating biotic resistance of such communities and, possibly, creating opportunities for further invasions [18,19,23]. Furthermore, a recent study found an invasive plant to strongly affect the functional composition of native communities during early stages of development [34].…”
Section: Effects On Plant Emergence and Aboveground Biomassmentioning
confidence: 99%
“…In contrast to numerous studies that assessed impacts of alien tree species on vascular plants, studies focused on bryophytes are scarce and lead to ambiguous conclusions (e.g. Taylor et al 2016;Sitzia et al 2018;Slabejová et al 2019). Moreover, most of them were focused on epiphytes, indicating, for example, high species richness of bryophytes on the bark of Robinia pseudoacacia (Jagodziński et al 2018;Fudali and Szymanowski 2019) or Q. rubra (Woziwoda et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…species that shape habitats and/or cause changes to their state and resources availability (Vitousek 1986;Schmitz et al 1997;Jones et al 1997;Crooks 2002;Başnou 2009;Başnou and Vilá 2009;Djurdjevic et al 2011;Benesperi et al 2012;Cierjacks et al 2013;Vítková et al 2017;Lazzaro et al 2018). The replacement of native species by alien plants, even when apparently ecologically equivalent, almost always negatively affects the ecosystems, especially if those species act as "ecosystem engineers" (Brown et al 2006;Wilson and Ricciardi 2009;Lazzaro et al 2018;Sitzia et al 2018;Uboni et al 2019).…”
Section: Resultsmentioning
confidence: 99%